The Community Awareness and Perceptions about Buruli Ulcers in Owerri, South-Eastern Nigeria - CHIGOZIE DIVINE, ONWUKA; EVANGELINE TOCHI, OPARAOCHA; eunice anyalewechi, nwoke; olivia chioma, onwuka (Journal of Medical Care Research and Review, 2021)
Community understanding and expectations of the cause and ultimately the necessary intervention to cure an illness decide who, when stuck down with a disease, people turn to for guidance, support, information, and care. The role of the community in the etiology, explanation, prognosis, and preferred method of treatment cannot be stressed because it offers in-depth knowledge on the burden of the disease, the local understanding of the causes of the disease, and therefore its management. The goal of the research was to determine the knowledge and perceptions of the community about Buruli ulcer (BU) and how to prevent Buruli ulcer in Owerri, South-Eastern, Nigeria. The survey questionnaire was used as a data collection method to request information on community understanding and community views of Buruli ulcer. Systematic sampling to select 600 participants for the study was used in the selection of participants for the group survey. Standard bacteriological and physical examination techniques were used to confirm Buruli ulcer cases. The research revealed a high level of awareness in the selected endemic communities (96.7%) about Buruli ulcer. However, patients with Buruli ulcer were considered to be people who were bewitched (48.3%). Others (14.3%) blamed them as individuals who did not take good care of themselves, while others (21.7%) found individuals afflicted with Buruli ulcer to have natural wounds. Further findings revealed two causes of Buruli Ulcer, natural causes (25.0%), and supernatural causes (63.3%). It was observed that going to the hospital is synonymous with an illness that is perceived to be triggered by natural variables, whereas a conventional healer would treat an illness that is perceived to have been induced by sorcery to combat the sorcery. The result also indicates that while there was a high awareness among community members in the study area of signs and symptoms of Buruli ulcer, their understandings and perceptions of its causative factors differed from those of biomedical understandings. Based on the results of the study, it is recommended that community outreach and education on the treatment and management of Buruli ulcer should be continued on a sustainable basis in the endemic communities. Keywords: Buruli Ulcer, Awareness, Perceptions, Reactions